Neonatal outcome and congenital malformations in children born after in-vitro fertilization - Koivurova, Sari; Hartikainen, Anna-Liisa; Gissler, Mika; Hemminki, Elina; Sovio, Ulla; Järvelin, Marjo-Riitta (Human Reproduction, 2002)
BACKGROUND: To evaluate the neonatal outcome and the prevalence of congenital malformations in children born after IVF in northern Finland we carried out a population-based study with matched controls. METHODS: Firstly, 304 IVF children born in 1990–1995 were compared with 569 controls, representing the general population in proportion of multiple births, randomly chosen from the Finnish Medical Birth Register (FMBR) and matched for sex, year of birth, area of residence, parity, maternal age and social class. Secondly, plurality matched controls ( n = 103) for IVF twins ( n =103) were randomly chosen from the FMBR and analysed separately. Additionally, IVF singletons ( n = 153) were compared with singleton controls ( n = 287). Mortality rates were compared with national figures from FMBR. RESULTS: Most mortality rates were twice as high as national figures in the general population. When compared with the control group representing the general population, the incidences of preterm birth [odds ratio (OR) 5.6, 95% confidence interval (CI) 3.7–8.6], very low birth weight (OR 6.2, 95% CI 2.0–19.0), low birth weight (OR 9.8, 95% CI 5.6–17.3), neonatal morbidity (OR 2.4, 95% CI 1.7–3.4) and hospitalization (OR 3.2, 95% CI 2.2–4.6) were significantly higher in the IVF group. The prevalence of heart malformations was four-fold in the IVF population than in the controls representing the general population (OR 4.0, 95% CI 1.4–11.7). CONCLUSIONS: Neonatal outcome after IVF is worse than in the general population with similar maternal age, parity and social standing, mainly due to the large proportion of multifetal births after IVF. The higher prevalence of heart malformations does not solely arise from multiplicity but from other causes. In order to improve neonatal outcome after IVF, the number of embryos transferred should be limited to a minimum.